Adolescent Smoking Susceptibility in the Current Tobacco Context: 2014–2016 - Owotomo, Olusegun (Am J Health Behav, 2018)
OBJECTIVES: We examined perceptions and behaviors associated with smoking susceptibility among adolescents in the current tobacco landscape. METHODS: Participants were 8th and 10th grade never-smokers of conventional cigarettes (N = 19,853) from Monitoring the Future surveys (2014–2016). Using weighted multivariable logistic regression, we examined risk factors for smoking susceptibility: alternative tobacco product use (e-cigarettes, large cigars, little cigars/cigarillos, and flavored little cigars/cigarillos), ownership of tobacco promotional items (TPIs), access to cigarettes, perceived influence of antismoking advertisements, and perceived addictiveness of conventional cigarette smoking. RESULTS: Among never-smokers of conventional cigarettes, 16.7% were susceptible to smoking, 6.2% were past 30-day alternative tobacco product users, and 3.5% owned TPIs. Alternative tobacco product use, ownership of TPIs, and easy access to cigarettes were associated with increased likelihood of smoking susceptibility. Perceived great influence by antismoking ads and higher perceived addictiveness of conventional cigarette smoking were associated with lower odds of smoking susceptibility. CONCLUSION: Alternative tobacco product use, ownership of TPIs, easy access to cigarettes, low influence by antismoking ads, and low perceptions of the addictiveness of conventional cigarettes are significant and actionable risk factors for smoking susceptibility among today’s adolescents.